Pengaruh Augmented Reality Marketing, Online Customer Review, Persepsi Harga terhadap Purchase Decision dan Repurchase Intention (Studi pada Konsumen Maybelline Official Store di Shopee) - Hapshoh, Nabilah Adawiyah Al; Wusko, Any Urwatul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study was conducted to determine the effect of Augmented Reality Marketing, Online Customer Review, Price Perception on Purchase Decision and Repurchase Intention (Study on Maybelline Official Store Consumers at Shopee)